The contribution of integrated and non-integrated pig farms to epidemiological dynamics of porcine reproductive and respiratory syndrome virus in Italy - M. Ustulin; D. Vio; C. Targhetta; C. Zanon; L. Ferino; G. Faustini; G. Franzo (Scientific Reports)
Abstract Porcine reproductive and respiratory syndrome (PRRS) is a global challenge for swine production. Due to its high variability and limited cross-protection, immune-based control measures are only partially effective, emphasizing the critical role of biosecurity. A prior study on Italy’s largest integrated pig production company demonstrated the effectiveness of hierarchical organization in separating pig flows but, through biostatistical estimations, highlighted vulnerabilities, particularly the role of non-integrated farms in introducing new variants into the integrated system. Over 500 PRRSV sequences from integrated and non-integrated farms in central-northern Italy were analysed in the present study using phylogenetic, phylodynamic, and phylogeographic approaches. Two main PRRSV clades were identified circulating in both systems, with non-integrated farms hosting a broader viral population. The migration rate of PRRSV from non-integrated to integrated systems was found to be 2–10 times higher than the reverse, depending on the clade. Geographical migration patterns and environmental factors influencing viral dispersal were evaluated. Despite being located in the same geographical areas, non-integrated farms exhibited higher viral dispersal speeds, marked by bursts over time. Although some differences in geographical persistence and dispersal risk factors were observed among clades and categories, road networks and pig population density were the most important and shared determinants. These findings confirm the critical role of non-integrated farms in PRRSV epidemiology, posing a risk to integrated systems due to their distinct persistence and spread determinants. The study underscores the necessity for regional collaboration and information sharing to improve infection control and reduce viral recirculation between different productive systems.